In the Light of Logic. - Feferman, Solomon (Oxford University Press, 1999)
This volume brings together a revised and annotated selection of Solomon Feferman's most important writings, covering the relation between logic and mathematics, proof theory, objectivity and intentionality in mathematics, and key issues in the work of Godel, Hilbert and Turing.